Comparative analysis of lysyl oxidase (like) family members in pulmonary fibrosis - Verena Aumiller (Nature Portfolio, 2017)
Abstract Extracellular matrix (ECM) composition and stiffness are major driving forces for the development and persistence of fibrotic diseases. Lysyl oxidase (LOX) and LOX-like (LOXL) proteins play crucial roles in ECM remodeling due to their collagen crosslinking and intracellular functions. Here, we systematically investigated LOX/L expression in primary fibroblasts and epithelial cells under fibrotic conditions, Bleomycin (BLM) induced lung fibrosis and in human IPF tissue. Basal expression of all LOX/L family members was detected in epithelial cells and at higher levels in fibroblasts. Various pro-fibrotic stimuli broadly induced LOX/L expression in fibroblasts, whereas specific induction of LOXL2 and partially LOX was observed in epithelial cells. Immunohistochemical analysis of lung tissue from 14 IPF patients and healthy donors revealed strong induction of LOX and LOXL2 in bronchial and alveolar epithelium as well as fibroblastic foci. Using siRNA experiments we observed that LOXL2 and LOXL3 were crucial for fibroblast-to-myofibroblast transition (FMT). As FMT could only be reconstituted with an enzymatically active LOXL2 variant, we conclude that LOXL2 enzymatic function is crucial for fibroblast transdifferentiation. In summary, our study provides a comprehensive analysis of the LOX/L family in fibrotic lung disease and indicates prominent roles for LOXL2/3 in fibroblast activation and LOX/LOXL2 in IPF.